2016
DOI: 10.1021/jacs.6b00515
|View full text |Cite
|
Sign up to set email alerts
|

Robust Chemical Synthesis of Membrane Proteins through a General Method of Removable Backbone Modification

Abstract: Chemical protein synthesis can provide access to proteins with post-translational modifications or site-specific labelings. Although this technology is finding increasing applications in the studies of water-soluble globular proteins, chemical synthesis of membrane proteins remains elusive. In this report, a general and robust removable backbone modification (RBM) method is developed for the chemical synthesis of membrane proteins. This method uses an activated O-to-N acyl transfer auxiliary to install in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 77 publications
(48 reference statements)
1
56
0
2
Order By: Relevance
“…46,47 Building on this work, Liu’s group recently published a method to introduce removable backbone modifications (RBMs) via a salicylaldehyde derivative. 48 …”
Section: Introductionmentioning
confidence: 99%
“…46,47 Building on this work, Liu’s group recently published a method to introduce removable backbone modifications (RBMs) via a salicylaldehyde derivative. 48 …”
Section: Introductionmentioning
confidence: 99%
“…Similar phenomena were reported in cases of some highly hydrophobic proteins. 29,30 The isolated final protein was analyzed on SDS−PAGE with the Ub fragment, 6, and the full ISG15-thioester, 5b ( Figure 2F). The SDS gel showed that the isolated final protein has a mass that ranged between 25 and 35 kDa, which corresponds to our final ISG15-Ub hybrid chain molecular weight.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition to overcoming steric hindrance that resulted in different coupling steps, backbone amide substitution also effectively disrupted peptide aggregation by weakening the interchain hydrogen‐bonding network. This strategy was further developed by the groups of Johnson, Offer, and Liu . It is worth noting that the group of Liu extended the approach by introducing a solubilizing tag onto the auxiliary benzyl group that empowered the synthesis and handling of small to medium‐sized membrane proteins with multiple transmembrane domains (Scheme C).…”
Section: Application Of Isoacyl Structural Motifs In Synthetic Peptidmentioning
confidence: 99%
“…This strategy was further developed by the groups of Johnson, [59] Offer, [60] and Liu. [61] It is worth noting that the group of Liu extended the approach by introducing as olubilizing tag onto the auxiliary benzyl group that empowered the synthesis and handling of small to medium-sized membrane proteins with multiple transmembrane domains (Scheme 4C). The tag was attached after completion of the target peptide assembly and anchored at the aniline amine, which was newly generated by the reduction of the nitro group.…”
Section: Application Of Isoacyl Motifs In Assisting Amide-bond Formationmentioning
confidence: 99%